Circulating plasma-derived extracellular vesicles expressing bone and kidney markers are associated with neurocognitive impairment in people living with HIV - Marques de Menezes, Erika G.; Bowler, Scott A.; Shikuma, Cecilia M.; Ndhlovu, Lishomwa C.; Norris, Philip J. (Frontiers in Neurology, 2024)
Background: Although effective antiretroviral therapy (ART) has improved the life expectancy of people with HIV (PWH), the prevalence of milder forms of HIV-associated neurocognitive disorders (HAND) persist, and it is associated with systemic and neuro-inflammatory processes that could impact other organ systems. However, the complex signaling mechanisms between the bone-kidney systems and the brain in HAND remain unknown. Extracellular vesicles (EVs) play a potential role in inter-organ communication and are involved in regulating cell activity in distant tissues. In this study, we examined whether levels of EVs from bone- and kidney-related cells associate with cognitive dysfunction and explored the relationship between kidney-bone EV axis in PLW experiencing cognitive deficits. Methods: EV subtypes were characterized in plasma from 61 PWH with either cognitive impairment (CI, n=53) or normal cognition (NC, n=8) based on the American Academy of Neurology criteria for HIV-associated dementia (HAD, n=11), minor cognitive motor disorder (MCMD, n=25) or asymptomatic neurocognitive impairment (ANI, n=17) by spectral flow cytometry. EVs were profiled with markers reflecting bone and kidney cell origin. A support vector machine learning-based model was employed for analyses of EV phenotypes to predict the cognitive dysfunction. Results: Plasma-EVs expressing osteocalcin, sclerostin, and nephrin were significantly higher in the cognitive impairment group compared to the normal cognition group. EVs bearing kidney cell markers correlated significantly with bone-derived EVs. A machine learning-based model, comprised of osteocalcin+, nephrin+, and CD24+ EVs predicted cognitive impairment in PWH on ART. Conclusions: Our study reveals that neurocognitive impairment in PWH is associated with increased levels of plasma EVs enriched with the bone markers osteocalcin and sclerostin and the kidney marker nephrin, suggesting that these EV subtypes may be novel candidate biomarkers for disease-spanning neurocognitive dysfunction. Moreover, the relationship between bone-derived EVs with kidney-derived EVs may suggest their role in mediating inter-organ crosstalk in the pathogenesis of HIV-associated cognitive impairment.